How Does Patient Socioeconomic Position Affect Breast Cancer Surgical Treatment and Mortality?: A Rapid Review - Schubbe D (Dove Medical Press, 2021)
Danielle Schubbe,1 Renata W Yen,1 Marie-Anne Durand1– 3 1The Dartmouth Institute for Health Policy and Clinical Practice, Dartmouth College, Lebanon, NH, USA; 2UMR 1295, CERPOP, Université de Toulouse, INSERM, Université Toulouse II Paul Sabatier, Toulouse, France; 3Unisanté, Centre universitaire de médecine générale et santé publique, Lausanne, CH-1011, SwitzerlandCorrespondence: Danielle SchubbeThe Dartmouth Institute for Health Policy and Clinical Practice, 1 Medical Center Drive, Williamson Translational Research Building, Level 5, Lebanon, NH, 03756, USATel +1 214 477-7986Email danielleschubbe@gmail.comBackground: Breast cancer is the second leading cause of death in women across the world. Despite significant improvements in overall breast cancer survival, disparities still exist. Research shows that socioeconomic position (SEP) plays a strong role in disparities in breast cancer care. Lower SEP can be a predictor of poorer breast cancer health outcomes and treatment received. No recent review has focused on SEP and breast cancer surgery outcomes. We conducted a rapid review assessing how patient SEP affects breast cancer surgical outcomes.Methods: We developed and ran the search strategy in Ovid MEDLINE in January 2021. We assessed study eligibility using an adapted version of PICOS criteria. We included observational studies that assessed the relationship between SEP and breast cancer surgery treatment, including outcomes like surgery choice, survival, and wait time to surgery. We independently reviewed each article and independently extracted data using a pre-designed form. One reviewer narratively synthesized the data extracted from the included articles.Results: We found twelve articles that met inclusion criteria. Eight out of 12 articles showed a difference in breast cancer surgery outcomes based on at least one measure of SEP. Six out of eight articles that collected surgery choice data found that women with lower SEP had lower rates of breast conserving surgery. One out of three articles that collected survival data found that higher SEP had a positive effect on survival. Additionally, one article that collected wait time to surgery data found a significant correlation between lower SEP and longer delays to surgical treatment.Conclusion: In conclusion, our rapid review of SEP and breast cancer surgery outcomes found that there is a relationship between SEP and breast cancer surgery choice. This rapid review did not find enough evidence to see a relationship with overall survival and wait time to surgery.Keywords: breast cancer, socioeconomic position, disparity, review